2016
DOI: 10.5539/jpl.v9n1p21
|View full text |Cite
|
Sign up to set email alerts
|

Governance and Constitutional Issues in the Nigerian Local Governments

Abstract: A challenge gaining momentous notoriety in the discourse of governance crisis is the pattern of underperformance at the grassroots. This paper delved critically into the factors that accounts for this oft-touted performance crisis, with emphasis on areas of the discourse not hitherto examined. Focusing on peculiar characteristic of the Nigerian state, its 'unitarised' federalism occasioned by prolonged military administrations, regional politicking, and constitutional subjugation into excessive control from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…It is the content of the law passed by the State House of Assembly and assented by the State Governor that establishes the offices to vie in the local government elections. The offices are categorized into two; Local Government Chairman (together with the Vice Chairman) and Councillors (Olaiya, 2016). In addition to the offices, the tenure and qualifications for the two positions are also clearly stated in the enabling law.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the content of the law passed by the State House of Assembly and assented by the State Governor that establishes the offices to vie in the local government elections. The offices are categorized into two; Local Government Chairman (together with the Vice Chairman) and Councillors (Olaiya, 2016). In addition to the offices, the tenure and qualifications for the two positions are also clearly stated in the enabling law.…”
Section: Resultsmentioning
confidence: 99%
“…The rationale for the discretionary powers of the Assembly is to take care of the https://dx. doi.org/10.15405/epsbs.2018.12.03.18 Corresponding Author: Musa Adamu Aliyu Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 205 peculiar needs of the local populace (Olaiya, 2016). For ease of comprehension, the functions of the local government councils have been classified into two; the exclusive and concurrent functions (Isa, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…It runs contrary to the findings from some works that submitted that education is better funded from the statutory allocation (Khemani, 2001;Akeem, 2011;Ikeji, 2011;Oseni, 2012). For Olaiya, (2016), Lamidi and Fagbohun (2013) and Khemani (2001), the Nigerian local government can only fare better in service delivery with increased statutory allocation from the federation accounts. Nevertheless, the findings are in tandem with notable works like Ubogu (2011), who found that funding education in Nigeria should involve contributions from all stakeholders in the form of taxes and other internally generated revenue.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…In The judicial arm consists primarily of magistrates' courts and traditional courts. These latter often adjudicate on issues such as inheritance and family disputes, and are headed by local traditional rulers (Olaiya 2016).…”
Section: Historical Development Of Local Government In Nigeriamentioning
confidence: 99%